(untitled) (CIPEEX, 2026)
Introduction: Neurodivergent students, including those with autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), or dyslexia, face significant barriers in medical education, ranging from learning difficulties to institutional stigma. Despite progress in the understanding of neurodiversity, educational policies remain poorly adapted to their needs. Objective: To identify and group neurodivergent medical students with shared characteristics, raising awareness of their challenges and supporting inclusive educational practices. Methods: A literature review was conducted on national and international studies addressing the experiences of neurodivergent students in medical education. Inclusion criteria were full-text availability, relevance to the topic, publication between 2014 and 2024, and language (Portuguese, English, or Spanish). Articles were selected from PubMed, SciELO, and LILACS databases using the descriptors “neurodivergent,” “learning disorder,” and “students,” combined with Boolean operators AND and OR. Results: Findings were grouped into five categories: (1) neurodiversity and mental health; (2) accessibility in education and work; (3) stigma and cultural perceptions; (4) learning aspects; and (5) interventional mechanisms. Studies reported high prevalence of depression and anxiety among neurodivergent students and physicians, persistent academic challenges, limited institutional support, and insufficient training to address neurodivergent patients. Conclusion: Assistive technologies, curricular adaptations, and psychological support demonstrated effectiveness in reducing barriers. These results emphasize the urgency of inclusive policies and further research to ensure equity in medical education. Keywords: Neurodivergence; Medical Education; Educational Inclusion.